1999
DOI: 10.1051/aas:1999100
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of optical seeing on the high antarctic plateau

Abstract: Abstract.Results from the 1995 season of site-testing experiments at the South Pole are presented, in which the seeing was measured using balloon-borne microthermal probes. Our analysis shows a marked division of the atmosphere into two characteristic regions: (i) a highly turbulent boundary layer (0 − 220 m) associated with a strong temperature inversion and wind shear, and (ii) a very stable free atmosphere. The mean seeing, averaged over 15 balloon flights, was measured to be 1.86 , of which the free atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 12 publications
9
100
2
Order By: Relevance
“…We found a median value of 3.9 , which is slightly lower than the 5.7 found by Lawrence et al (2004) with MASS but still very competitive compared to more classical sites (Table 1 of Lawrence et al 2004). Our value is very close to the South Pole isoplanatic angle of 3.2 as estimated by Marks et al (1999) from in situ radio soundings. This is not surprising; the isoplanatic angle expressed as a weighted integral over the vertical distribution of turbulence is…”
Section: Isoplanatic Anglesupporting
confidence: 86%
See 2 more Smart Citations
“…We found a median value of 3.9 , which is slightly lower than the 5.7 found by Lawrence et al (2004) with MASS but still very competitive compared to more classical sites (Table 1 of Lawrence et al 2004). Our value is very close to the South Pole isoplanatic angle of 3.2 as estimated by Marks et al (1999) from in situ radio soundings. This is not surprising; the isoplanatic angle expressed as a weighted integral over the vertical distribution of turbulence is…”
Section: Isoplanatic Anglesupporting
confidence: 86%
“…Both sites of Dome C and South Pole actually exhibit strong winds in winter above 10 km (Marks et al 1999;Trinquet et al 2008a). Figure 19 shows the dependence of θ 0 on the period of the year.…”
Section: Isoplanatic Anglementioning
confidence: 99%
See 1 more Smart Citation
“…If this layer appears to be an excessively difficult obstacle at the South Pole site, with a thickness of more than 200 m (Marks et al 1996(Marks et al , 1999, its much reduced thickness at Dome C (around 30 m, as it appears now both from models and from measurements) makes it a real difficulty, but not an insurmountable problem. Different strategies must be studied to make it possible to exploit the unique seeing encountered up there, either to set up the most demanding instruments at 30 m, or to use highly performing adaptive optics that must solve an unusual but probably not so difficult problem with a unique turbulent layer located extremely close , LeLouarn & Hubin 2006.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…In 1991-92 Gillingham suggested that exceptionally good seeing could be expected above the high part of the Antarctic Polar Plateau. A preliminary site testing campaign was done at Dome C in 1996 (Marks et al 1999).…”
Section: Introductionmentioning
confidence: 99%